Ways of identification and challenges in translation of Rafael Correa’s sexist addresses in political discourse. - Rios Pulgar, María Andrea (2018)
In recent times, news from women who have suffered some kind of abuse are talked about everywhere. Many people are not aware that sexist language is a form of abuse. The problem arises in societies that are so used to that kind of language that they do not identify it as something harmful. The situation becomes even more complex if this sexist language is used by political leaders or public figures, who are called to serve as role models to society, such as former president of Ecuador Rafael Correa Delgado. Due to this, within the scope of translation, the problem lies in the lack of a tool to identify this type of language. This paper offers translation proposals and appropriate strategies to manage all challenges for such translation. The first phase of this project consisted of an exploration of topics related to language, language in relation to gender and sexism within language. Then, the ambivalent sexism theory proposed by Glick was chosen to design a table with objective parameters of levels, and types of sexist language. These strategies were used to analyze some addresses taken from the political discourse of Rafael Correa, and translation proposals were offered for them. It was found that Rafael Correa performs addresses claimed as sexist by feminist groups.